Selected Literary and Resourceful Websites of Urdu: A Survey - Muhammad Mohsin Khan; Dr. Hammad Rasool (بازیافت)
This article reveals round the literary and informative websites of Urdu Language and literature. In this, we discuss these website whose play important role in the promotion of Urdu language and literature. With the usage of these Urdu websites, we can easily access the international literature and information of different Universities, Organization, Institutes and etc.